Detection of Facial Micro Expressions and Textual-Tracking for Paralyzed Using Computer Vision - Mathad, Sameer G; Pruthvi, LR; Sanjana, CS; B, Akash; Deepthi, VS (International Journal of Computer Sciences and Engineering, 2019)
Paralysis is the loss of voluntary muscle control. Many people cannot move a single part of their body. Even though the paralyzed people are cognitively aware of their surroundings, they have no means of communication. The paralyzed people have lost their ability to talk, type, etc. These victims affected by Locked-In Syndrome have their thoughts and ideas trapped inside of them. Usually people with paralysis have total control over their eye movement. Therefore this project aims to build a real time interactive eye blink system that allows paralyzed people to easily express themselves. Some people who are affected with Amyotrophic Lateral Sclerosis (ALS) and Tetraplegia can also express their emotions (Eg: smile) and hence these expressions can be used as commands for performing some helpful tasks. We aim to show this by implementing sentiment-based music system to play music by retrieving their current mood via video streams.